ANALISIS RELEVANSI KONSEP KEADILAN SOSIAL DALAM QS. AN-NISA AYAT 135 MENURUT TAFSIR AL-MISBAH DENGAN TEORI KEADILAN SOSIAL JOHN RAWLS - Syafa Safinatul Hayya (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study discusses the concept of social justice from an Islamic perspective through M. Quraish Shihab's interpretation of QS. An-Nisa verse 135 in Tafsir Al-Misbah and relates it to John Rawls's theory of social justice. The background of this study is the phenomenon of social injustice that is still rife, such as corruption, nepotism, discrimination, and economic inequality, which emphasizes the importance of discussing justice in both philosophy and religion. This study uses a qualitative approach with a library research type. The method used is This study uses a thematic analysis method that will be used to examine QS. An-Nisa verse 135 in Tafsir Al-Misbah and relate it to John Rawls's theory of social justice. The data collection technique in this study is carried out through documentation studies or library research. The results of the study show a meeting point between the two, namely an emphasis on objective justice, equal rights, and protection for weak groups. However, there are also fundamental differences: Quraish Shihab positions justice as a divine command with spiritual value, while Rawls bases it on rational agreement in a pluralistic society. The relevance of these two views makes a significant contribution to building a more just society in the legal, social, economic, and leadership fields.